Estudio comunicacional de la construcción de la agenda mediática en ECUADOR TV - Escobar Salazar, Christian Paúl (2013)
Historically, programming has been determined by various situations, as may be the editorial line, the ownership structure, the rating, etc, in that sense all programming has some intentionality and directionality, in other words, it is not neutral. From this consideration we research to know the preferences of the TV viewers of Ecuador TV, through a theoretical analysis and practical being indispensable to complement it with opinion polls, surveys and in-depth interviews from the source. The structure of such agenda, points out the search for the otherness to forge the common good, strengthening the educational theme so that the children are educated from their localities, even for those who are in vulnerable environments.